Asthma Control and Cognitive Function in a Cohort of Elderly Adults. Issue 4 (8th April 2015) - Ray, Maile; Sano, Mary; Wisnivesky, Juan P.; Wolf, Michael S.; Federman, Alex D.
Abstract : Objectives: To determine whether poor asthma control is associated with cognitive impairment in a cohort of older, inner‐city adults with asthma. Design: Prospective observational cohort study. Setting: Outpatient practices in New York City and Chicago. Participants: Individuals aged 60 and older with a physician diagnosis of asthma and without chronic obstructive pulmonary disease or a smoking history of 10 pack‐years or more (N = 452). Measurements: Cognitive assessments that included processing speed (pattern comparison, Trail‐Making Test Part A), executive function (Trail‐Making Test Part B), attention and working memory (letter number sequencing), immediate and delayed recall (Wechsler Memory Scale Story A), word fluency (animal naming), and global cognitive function (Mini‐Mental State Examination) were administered. Asthma control was measured using the Asthma Control Questionnaire (ACQ) and airway obstruction using spirometry as the predicted forced expiratory volume at 1 second (FEV1 ) of less than 70%. Cognitive measures were modeled in linear and logistic regression models controlling for age, race, education, English proficiency, and income. Results: Participants had a mean age of 68; 41% had poor asthma control according to the ACQ, and 35% had FEV1 of less than 70%. Poor asthma control and FEV1 less than 70% were significantly associated with all measures of cognitive function in univariate analyses, although these associations lost their statistical significance after adjusting for age, education, English proficiency, and other covariates. The same pattern was observed when the outcomes were below‐normal performance on the cognitive measures based on normative data. Conclusion: Poor asthma control and airway obstruction are not associated with poor performance on various measures of cognitive function in older adults with asthma.